2022
DOI: 10.3389/fmars.2022.973364
|View full text |Cite
|
Sign up to set email alerts
|

Benthic community zonation from mesophotic to deep sea: Description of first deep-water kelp forest and coral gardens in the Madeira archipelago (central NE Atlantic)

Abstract: The Madeira archipelago has a unique underwater landscape that is characterised by narrow shelves, steep slopes and a large submarine tributary system that boosts primary productivity in oligotrophic waters and thus offers a potential for hotspots of biodiversity. Despite this, there have been limited deep-water exploration activities with less than five expeditions since the 1960s. Here, we investigated the seabed on the southern side of the Madeira-Desertas Ridge using a manned submersible along a 3.8 km lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…maiteae (Santos et al, 2016), and several endemic coral (Cavalcanti et al, 2013;Pereira-Filho et al, 2015Amado-Filho et al, 2016;Negrão et al, 2021) and fish species (Moura et al, 2021). In the Mediterranean, the endemic deep-water kelp Laminaria rodriguezii (Barbera et al, 2003) and several species of endemic sponges (Longo et al, 2020) can be found on rhodolith beds, while in the NE-Atlantic the rare kelp L. ochroleuca and several rare rhodolith-associated seaweeds have been recorded (Peña et al, 2014;Braga-Henriques et al, 2022;Helias and Burel, 2023). At Cocos Island, Costa Rica, a new and endemic octocoral species, Rhodolitica oculta, has been found in association with rhodoliths (Breedy et al, 2021).…”
Section: Uniqueness or Raritymentioning
confidence: 99%
“…maiteae (Santos et al, 2016), and several endemic coral (Cavalcanti et al, 2013;Pereira-Filho et al, 2015Amado-Filho et al, 2016;Negrão et al, 2021) and fish species (Moura et al, 2021). In the Mediterranean, the endemic deep-water kelp Laminaria rodriguezii (Barbera et al, 2003) and several species of endemic sponges (Longo et al, 2020) can be found on rhodolith beds, while in the NE-Atlantic the rare kelp L. ochroleuca and several rare rhodolith-associated seaweeds have been recorded (Peña et al, 2014;Braga-Henriques et al, 2022;Helias and Burel, 2023). At Cocos Island, Costa Rica, a new and endemic octocoral species, Rhodolitica oculta, has been found in association with rhodoliths (Breedy et al, 2021).…”
Section: Uniqueness or Raritymentioning
confidence: 99%